Screening of HIV Infection in Patients with Pulmonary Tuberculosis at a Tertiary Care Hospital - Abdul Rashid Dayo, Shahzad Memon, Yar Muhammad Tunio, Kashif Ali, Maria Basheer, Ruqayya Farhad, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of HIV infections in patients with pulmonary tuberculosis. Patients and methods: This cross-sectional study, was conducted at the Department of Medicine, Ghulam Muhammad Mehar Medical College, Sukkur, from October 2019 to 2020. All the patients had pulmonary TB of any duration; their ages ranged from 15 years to 45 years, and both genders were included. Sputum analysis for the patients with known pulmonary tuberculosis was done for AFB (Positive/Negative). Sputum was also sent for a GeneXpert test for the diagnosis of MDR TB. The patient's sputum culture and sensitivity were checked from the record and the XDR TB, if present in that record, was noted. In all patients with PTB, blood was taken and sent for serology. HIV was assessed by serology. All of the data was taken and recorded into the proforma at its completion, and was then analyzed by SPSS version 26 for the research purpose. RESULTS: The average age of the patients was 34.2±10.3 years, and the average duration of TB was 8.1±3.9 months. Out of all, 90 (64.3%) were males and 50 (35.7%) were females. In distribution for types of pulmonary tuberculosis, 1st line drug response was found in 41 (29.4%) patients, MDR TB in 60 (42.8%), while XDR TB was found in 39 (27.8%) patients. HIV infection serology was found to be positive in 53 (37.9%) patients. As per stratification, the HIV serological infection was significantly higher among males (p-0.004), while it was statistically insignificant according to the patients' age and disease status (p->0.05). CONCLUSION: It was to be concluded that the prevalence of HIV infection was documented as considerably high in patients with pulmonary tuberculosis. Therefore, all individuals having tuberculosis should be evaluated for HIV risk factors and advised to get tested.